2000
DOI: 10.1007/s003810000340
|View full text |Cite
|
Sign up to set email alerts
|

Postraumatic intracranial hematomas in infancy

Abstract: The series revealed a greater incidence of post-traumatic ICH in boys (73.5%), whose average age was 6 years 5 months +/- 4 years 10 months (range 1 day to 15 years). Fifty-three percent of the girls suffered post-traumatic ICH before the age of 3, while 54% of the children were 7 years of age or older (P<0.05). Falls were the most frequent mechanism of injury causing CCT (36.3%), followed by vehicle accidents (33.6%) and unknown causes (15.9%), the latter mainly in children under 3 years old (31%). The most f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
2
4
1
Order By: Relevance
“…This finding coincides with a review reporting on a 16-year experience with posttraumatic intracranial haematomas, in which vomiting (45.7%) was the most frequent immediate symptom, beside loss of consciousness (Herrera et al, 2000). Another study on extradural haematomas in children found recurrent vomiting in 70% of the cases (Maggi et al, 1998).…”
Section: Discussionsupporting
confidence: 71%
“…This finding coincides with a review reporting on a 16-year experience with posttraumatic intracranial haematomas, in which vomiting (45.7%) was the most frequent immediate symptom, beside loss of consciousness (Herrera et al, 2000). Another study on extradural haematomas in children found recurrent vomiting in 70% of the cases (Maggi et al, 1998).…”
Section: Discussionsupporting
confidence: 71%
“…Another study demonstrated that the most common cause of severe head injury in early infancy (<12 months) was domestic accidents, mostly falls [15]. Vehicle accidents were the second most common cause of injury, a finding that is also consistent with the literature [13,15,16]. It has been well documented that abuse/inflicted injury in infants has specific clinical characteristics on its neuropathology, radiology and presentation [17,18,19,20].…”
Section: Discussionsupporting
confidence: 79%
“…The median incidence of fall injury in Asia in those aged 0–18 years was found to be 170 per 100 000 children averaging 43% of all injuries (Table S2) (see Tables S1 and S2 for citation of references 14–55). Among those less than 5 years in Asia there was a median incidence of 58.2 falls per 100 000 children, comprising 35% of all injuries.…”
Section: Resultsmentioning
confidence: 99%